Toward a phenomic analysis of chronic postsurgical pain following cardiac surgery. Issue 1 (1st January 2019) - Clarke, Hance; Rai, Ajit; Bao, James; Poon, Michael; Rao, Vivek; Djaiani, George; Beattie, Scott; Page, Gabrielle; Choiniere, Manon; McGillion, Michael; Parry, Monica; Hunter, Judith; et al.
ABSTRACT: Background: Despite the same surgical approach, up to 40% of patients develop chronic postsurgical pain (CPSP) following cardiac surgery, whereas the rest are chronic pain free. This variability suggests that CPSP is controlled partially through genetics, but the genes for CPSP are largely unknown. Aims: The aim of this study was to identify potential CPSP phenotypes by comparing patients who developed CPSP following cardiac surgery vs. those who did not. Methods: A research ethics board–approved, cross-sectional study of post–cardiac surgery pain was conducted at Toronto General Hospital from 2011 to 2015. Patients were recruited to complete a short survey of chronic pain scores and the Short-Form McGill Pain Questionnaire–2. A subset of patients completed a longer survey of eight validated pain phenotyping questionnaires and/or four psychophysical assessments. All surveys and psychophysical testing were conducted after surgery. Patients were stratified by presence of chronic pain and groups were compared using descriptive statistics. Results: Six hundred forty-three patients completed the short form survey. The mean postsurgery assessment time was 41.5 (SD = ±25.1) months. Over a quarter (27.8%) reported CPSP at the chest as a consequence of their surgery. Of patients reporting CPSP, 46.6% reported mild pain (0–3), 35.8% reported moderate pain (4–7), and 17.6% reported severe pain (7–10) in accordance with the numerical rating scale. Patients with moderate and/or severe CPSP were younger, had a greater body mass index, and had higher anxiety sensitivity, pain catastrophizing, and somatization scores. Conclusions: Chronic pain levels after cardiac surgery are associated with anxiety, catastrophizing, and sensory abnormalities in body parts outside the field innervated by injured nerves, indicating the presence of widespread central sensitization to incoming sensory inputs from intact nerves.